(untitled) (UNIZIK Journal of Marketing, 2024)
The study investigated the influence of Strategic internal marketing on staff performance in deposit money banks in Enugu State. The empirical investigation was conducted in the banking sector in Enugu state. A descriptive research was conducted, and a structured questionnaire was used for collecting data from the employees of deposit money banks in Enugu state. The data collection instrument was a structured questionnaire validated using expert opinion while Cronbach alpha was used to test the reliability of the instrument, whereupon all variables surpassed the benchmark 0.6. The data collected were analyzed using the Pearson’s products moment correlation coefficient and multiple regression statistical tools. The findings among others revealed that all dimensions of internal marketing understudy including training, communication, empowerment, and motivation have a positive and significant relationship with staff performance. Therefore, it was concluded that internal marketing activities significantly manifest among customer contact employees within the deposit money banks in Enugu state and these activities influence the staff’ performance. The researcher recommended among others that management of deposit money banks should key into the internal marketing activities in order to ensure improved performance of their staff.